The Effectiveness Of The Stroke Rehabilitation Model With Thai Traditional Medicine For Caregivers (Journal of Namibian Studies : History Politics Culture, 2023)
Stroke is the leading cause of long-term disability impacting patients’ daily lives. The patients need adequate long-term rehabilitation, according to the appropriate rehabilitation model essential to help them recover and resume their daily activities as close to normal as possible. This quasi-experimental research aims to study the effectiveness of the stroke patient rehabilitation model with Thai traditional medicine for caregivers. The sample study consisted of 60 pairs of caregivers and ischemic stroke patients in Nakhon Pathom Province, divided into experimental and comparison groups. Data were collected using questionnaires and analyzed by descriptive statistics and inferential statistics consisting of independent sample t-tests and paired sample t-tests at a significant level of 0.05. The results showed that after the trial, the experimental group had a higher limb muscle strength than the comparison group, and the level of limb pain was lower than the comparison group. In conclusion, the model of stroke patient rehabilitation with Thai traditional medicine by caregivers taken to their patients is effective, helps patients have better muscle strength levels, and can reduce muscle pain. Therefore, caregivers can use traditional Thai medicine such as massage, herbal compresses, and exercises to rehabilitate stroke patients and optimize rehabilitation on their own.